A Prospective study on Gastrointestinal Perforation Peritonitis in Andhra Pradesh, India - Dr. G. Someswara Rao; Dr. B. Visweswara Rao (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2020)
Introduction: Perforation is defined as an abnormal opening in a hollow organ or viscus. All over the world, perforation peritonitis is the most prevalent surgical emergency tackled and treated by a surgical team. The etiology leading to peritonitis in tropical countries shows a different spectrum from its western world. The present study was conducted to highlight the spectrum of hollow viscus perforation peritonitis in terms of etiology, clinical presentations, site of perforation, surgical treatment, postoperative complications, and mortality encountered.Methods: The study was a prospective observational study conducted from March 2016 to March 2019 in the Department of General Surgery, Great Eastern Medical School and Hospital, Andhra Pradesh. A total of 320 patients with perforation peritonitis were included in the study and underwent exploratory laparotomy.Results: Out of 320 patients, there were 276 males (86.25%) and 44 females (13.75%). Duodenal perforation was the most common type (34.38%), which was mainly due to Acid peptic disease followed by Jejunal and Ileal perforations. Wound infection was the most common complication. The mortality rate was 8.44% (27 patients).Conclusion: Early diagnosis, resuscitation with fluids, and timely surgical intervention are the most important factors deciding the fate of the patient with perforation peritonitis.